Improving Learning Outcomes of Dribbling in Football Games Through the Jigsaw-Type Cooperative Learning Model - Muhammad Hasbillah; Achmad Karim; Suparman Suparman (Universitas Majalengka, 2023)
This research is classroom action research conducted in four meetings in cycles I and IIÂ and is designed through four stages, namely planning, implementation, observation, and reflection. The data source for this research was 17 students in class V at SDN 35 Wewangrewu, Wajo Regency. Data collection on the ability to dribble using an assessment sheet for prefix techniques, body position, foot contact with the ball, and final attitude The results of a quantitative analysis of data on dribbling learning outcomes in football games showed that the number of students who completed the first cycle was 10 with a percentage of 58.82%, and the number of students who completed the second cycle was 17 with a percentage of 100%. Based on the results of this study, it can be concluded that learning physical education through the Jigsaw cooperative learning model can improve the learning outcomes of dribbling in football games for students at SDN 35 Wewangrewu, Wajo Regency.